The genetic and proliferation characterization analysis of novel coxsackievirus A12 in Beijing, China - Han, Zhenzhi; Jia, Liping; Zhu, Runan; Fu, Hanhaoyu; Lin, Chenbo; Huang, Hui; Deng, Li; Zhang, Jianzhao; Zhao, Linqing (Frontiers in Microbiology, 2025)
IntroductionCoxsackievirus A12 (CVA12) is a serotype of Enterovirus A. Its evolutionary and molecular characteristics remain poorly understood.MethodsThe metagenomic Next-Generation Sequencing (mNGS) strategy were used to investigate the viral diversity. The viral isolation, proliferation assays, phylogenetic relationships and recombination events were analyzed.ResultsIn this study, nine clinical specimens collected in Beijing, China, during March 2010 to October 2019 were identified as CVA12 positive, among which five were confirmed by mNGS. Then five CVA12 strains were isolated, and the proliferation assays demonstrated the preferential replication of CVA12 in rhabdomyosarcoma (RD) cells, with rapid intracellular replication before being released extracellularly, over Hep-2 cells. Transcriptomic profiling of infected RD cells revealed that the significant up-regulated genes were involved in inflammatory responses and transcriptional regulation (e.g., JUN, FOS), suggesting robust host immune activation. Phylogenetic analysis identified that four strains were clustered into genogroup E, indicating a lineage undergoing active transmission in Beijing, China, the other one into genogroups B. Recombination analysis revealed that strain s7275 exhibited recombination with CVA5 (strain 3,490, GenBank access number OK334538) at the breakpoint position 3,373–6,634, while the others showed recombination with EV-A71 (strain EV71/P1034/2013/China, GenBank access number KP289419) at breakpoint position 3,370–6,645.DiscussionThese findings underscored the genetic diversity and recombination dynamics which provided insights into the evolutionary implications of CVA12, and its proliferation features in RD cells of CVA12. Further research is needed to elucidate the functional mechanisms of CVA12 infection and its role for disease.